Comparison of the prognostic potential of biomechanic stress markers - circulating stromelysin-1, matrix metalloprteinase-9 and N-terminal fragment of brain natriuretic peptide in patients with acute Q-wave myocardial infarction. Results of cohort study - T. Samura (Zaporozhye State Medical University, 2012)
85 patients after documented Q-wave myocardial infarction (MI) were observed. Echocardiography was performed and circulating levels of such biomarkers as MMP-3, MMP-9 and NT-pro-BNP were detected on the day of hospitalization and diagnosis of acute IM, on 21 and 60 days after onset of acute MI. The analysis of revealed data has shown that increase of MMP-3 and MMP-9 above optimal cut-point (9.7 ng/ml and 18.1 ng/ml respectively) was closely associated with up of 1-year cardiovascular mortality risk in patients after Q-MI. Used in prognostic model analysis of content of circulating MMP-3 and MMP-9 is corelated with increase of positive prognostic value of both of them rising up to 70% (prognostic sensitivity and specify are 84% and 82% respectively).